Concentrations and Species of Mercury in Municipal Sludge of Selected Chinese Cities and Potential Mercury Emissions From Sludge Treatment and Disposal - Liu, Jing; Lin, Li; Wang, Keyun; Ding, Rui; Xie, Zhouqing; Zhang, Pengfei (Frontiers in Environmental Science, 2022)
Municipal sewage has been identified as an important source of mercury (Hg) to the environment, and sewage sludge is the major sink of sewage-borne Hg. Knowledge of Hg species in sludge and potential Hg emissions during sludge treatment/disposal is still limited. A survey on Hg concentrations and species in sewage sludge of 16 provinces and municipalities in China was conducted. Hg was detected in all sewage sludge samples, with total Hg (THg) concentrations ranging from 0.3 to 7.7 mg/kg. Results from sequential chemical extractions (SCE) indicated that sludge-borne Hg mainly occurred in the form of Hg sulfide, with a small amount of organo-chelated Hg (Hg-OM) and HgO, and a negligible amount of soluble Hg. Thermal decomposition results indicated that Hg is generally released from sludge at a temperature range of 200-400 °C, with the highest release at 250-350 °C (38%-86%), consistent with the thermal decomposition of HgS, Hg-OM, and HgO. THg in sewage samples under ventilation at room temperature remained constant over a month period, indicating negligible Hg emission under such conditions. The mass loading of sludge-borne THg in China for year 2019 was estimated to be 30 tons, about 2% of the total anthropogenic THg released (including direct and secondary anthropogenic releases) in China. At the temperature range for sludge incineration, sludge carbonization, and sludge/brick/cement production, most of the Hg in sludge will be released to air due to thermal decomposition of Hg compounds. As such, Hg-capture systems are essential in sludge treatment processes involving high temperatures.